A modeling framework for computational simulations of thoracic endovascular aortic repair. (28th February 2022) - Shahbazian, Negin; Doyle, Matthew G.; Forbes, Thomas L.; Amon, Cristina H.
Abstract: Thoracic endovascular aortic repair (TEVAR) is a minimally invasive treatment for thoracic aortic conditions including aneurysms and is associated with a number of postoperative stent graft related complications. Computational simulations of TEVAR have the potential to predict surgical outcomes and complications preoperatively. When using simulations for stent graft design and prediction of complications in a population, it is difficult to generalize patient‐specific TEVAR computational models due to patient variability. This study proposes a novel modeling framework for creating realistic population‐based computational models of TEVAR focused on aneurysms that allow for developing various clinically relevant geometric configurations and scenarios that are not easily attainable with limited patient data. The framework includes a methodology for developing population‐based thoracic aortic geometries and defining age‐dependent aortic tissue material models, as well as detailed steps and boundary conditions for finite element modeling of stent graft deployment during TEVAR. The simulation framework is illustrated for predicting the formation of a bird‐beak configuration, a wedge‐shaped gap at the proximal end of the deployed stent graft in TEVAR that leads to incomplete seal. A baseline TEVAR simulation model was developed along with three simulations in which the value of aortic curvature, aortic arch angle, or aortic tissue properties varied from the baseline model. Analyzing the length and angle of the bird‐beak configuration in each case shows that the bird‐beak size is sensitive to different values of the aortic geometry highlighting the importance of using realistic parameter values. Abstract : This study proposes a novel computational modeling framework for thoracic endovascular aortic repair (TEVAR) that includes developing realistic population‐based aortic geometries and age‐dependent aortic tissue material models, as well as detailed steps for TEVAR computational simulations. The framework is illustrated for predicting bird‐beak configuration (a proximal wedge‐shaped gap) formation in four TEVAR simulation cases with varying values of aortic geometric parameters and tissue properties, which result in different bird‐beak lengths and angles, highlighting the importance of using realistic parameter values.